Quality improvement for patients with hip fracture: experience from a multi-site audit. Issue 3 (1st September 2002) - Freeman, C; Todd, C; Camilleri-Ferrante, C; Laxton, C; Murrell, P; Palmer, C R; Parker, M; Payne, B; Rushton, N
Abstract : Problem: The first East Anglian audit of hip fracture was conducted in eight hospitals during 1992. There were significant differences between hospitals in 90-day mortality, development of pressure sores, median lengths of hospital stay, and in most other process measures. Only about half the survivors recovered their pre-fracture physical function. A marked decrease in physical function (for 31%) was associated with postoperative complications. Design: A re-audit was conducted in 1997 as part of a process of continuing quality improvement. This was an interview and record based prospective audit of process and outcome of care with 3 month follow up. Seven hospitals with trauma orthopaedic departments took part in both audits. Results from the 1992 audit and indicator standards for re-audit were circulated to all orthopaedic consultants, care of the elderly consultants, and lead audit facilitators at each hospital. Key measures for improvement: Processes likely to reduce postoperative complications and improve patient outcomes at 90 days. Strategy for change: As this was a multi-site audit, the project group had no direct power to bring about changes within individual NHS hospital trusts. Results: Significant increases were seen in pharmaceutical thromboembolic prophylaxis (from 45% to 81%) and early mobilisation (from 56% to 70%) between 1992 and 1997. There were reduced levels of pneumonia, wound infection, pressure sores, and fatal pulmonary embolism, but no change was recorded in 3 month functional outcomes or mortality. Lessons learnt: While some hospitals had made improvements in care by 1997, others were failing to maintain their level of good practice. This highlights the need for continuous quality improvement by repeating the audit cycle in order to reach and then improve standards. Rehabilitation and long term support to improve functional outcomes are key areas for future audit and research.